Children's attitudes towards the Irish language: A study of fifth and sixth class students in an English-medium primary school. - Ní Mhurchú, Niamh (My University, 2017)
The purpose of this research is to ascertain children's attitudes towards the Irish language. The study takes place in light of the launch of the 20-Year Strategy for the Irish Language 2010-2030 and the recent implementation of the new Primary Language Curriculum (DES, 2015; Government of Ireland, 2010). The researcher sought to investigate the impact of the school and home environments of children's attitudes towards the language. The researcher also examined children's motivation to learn Irish. Throughout, the researcher considered previous studies that have been carried out in this area while referring to relevant literature. Empirical research was carried out with forty fifth and sixth class students, attending an English-medium primary school. Through the use of a questionnaire the researcher collected data which was then analysed using descriptive and inferential statistics. The findings assert that respondents hold an overall negative attitude towards the teaching and learning of Irish. With 70% of respondents selecting Irish as either their first, second or third least favourite school subject. These findings give rise to recommendations relating to the teaching and learning of Irish in primary schools. The researcher recommends that further studies should be carried out in this area, that schools should reconsider their teaching methodologies and that initial teacher training should be improved.
Professional Masters of Education
Keywords: Research Subject Categories; Irish language; Primary Language Curriculum; School; Home environment; Teaching methodologies; Initial teacher training